2012
DOI: 10.1007/s11368-012-0590-1
|View full text |Cite
|
Sign up to set email alerts
|

How effectively does a single or continuous iron supply affect the phosphorus budget of aerated lakes?

Abstract: Purpose In lake restoration, the redox sensitivity of iron (Fe)-phosphorus (P) compounds has been regarded as detrimental for a sustainable increase in sedimentary P retention since developing low redox potentials release Fe-bound P. Thus, Fe salts alone have rarely been used successfully to inactivate sediment P, and there are no studies on the long-term effects of in-lake Fe applications on P retention. Here, we analyzed for how long, and how efficiently, a single and continuous Fe application can affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…The most compelling evidence that Fe treatment increases the long‐term sequestration of P in sediments comes from Lake Vadnais, Minnesota,USA (Engstrom ) and Lake Groß‐Glienicke, Germany (Kleeberg et al. , , Rothe et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most compelling evidence that Fe treatment increases the long‐term sequestration of P in sediments comes from Lake Vadnais, Minnesota,USA (Engstrom ) and Lake Groß‐Glienicke, Germany (Kleeberg et al. , , Rothe et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…These case studies demonstrate that Fe applications are logistically and financially feasible, at least in small-to medium-sized water bodies. The most compelling evidence that Fe treatment increases the long-term sequestration of P in sediments comes from Lake Vadnais, Minnesota,USA (Engstrom 2005) and Lake Groß-Glienicke, Germany (Kleeberg et al 2012, Rothe et al 2014). However, the success of Fe treatment as a remediation strategy is difficult to evaluate in many cases because studies are often confounded by the failure to control external sources of nutrients, absence of pre-treatment baseline data, insufficient Fe application doses, and/or simultaneous implementation of other remediation measures (e.g., food web biomanipulation, water column aeration, or other chemical sediment treatments).…”
Section: Discussionmentioning
confidence: 99%
“…Today, this shift is evident at a sediment depth of 23 cm. Both Fe and TP contents in the sediment almost doubled after the treatment, reaching 33 mg g −1 dry weight and 2.6 mg g −1 dry weight (Kleeberg et al, 2012). Due to the iron's redox sensitivity iron and TP contents are higher throughout the newly formed sediment which has accumulated since the in-lake treatment in 1992/93.…”
Section: Study Sitementioning
confidence: 99%
“…As claimed by Sas (1989), though, it might be that on an annual basis there is no net P release at all, but just an annual cycle. Kleeberg et al (2012Kleeberg et al ( , 2013) confirmed a comparable interaction in which [50 % of the earlier released Fe and P can coprecipitate within a couple of days during the lake's overturn. In stratified lakes, based on P:Fe:S ratios, an intact or disrupted ''ferrous wheel'' might control the net phosphorus release to the epilimnion.…”
Section: Other P Sourcesmentioning
confidence: 60%